Synthesis, Characterization, Nucleolytic, Antibacterial And Antiproliferative Properties Of Vanadium, Copper And Manganese Complexes - Lim, Eng Khoon (2011)
Series of vanadium carboxylato complexes, copper carboxylato complexes, manganese carboxylato complexes and vanadium phenanthroline derivative complexes have been synthesized and characterized. The details of all the complexes are tabulated in Table 2.2 (page 37). The complexes have been characterized by X-ray crystallography, elemental analysis, FT-IR, UV–Vis spectroscopy and cyclic voltammetry. In electrochemistry studies, vanadium carboxylato complexes show redox active by displaying a quasi-reversible redox couple corresponding to VV/VIV redox process while copper carboxylato complexes show redox active by displaying two quasi-reversible redox couples corresponding to CuIICuII/CuIICuI and CuIICuI/CuICuI redox processes and manganese carboxylato complexes show redox active by displaying a quasi-reversible redox couple corresponding to MnII/MnIII redox process. In nucleolytic studies, all the complexes can induce oxidative DNA cleavage but in different manner. The copper carboxylato complexes and manganese carboxylato complexes can induce DNA cleavage in the presence of H2O2. Meanwhile for vanadium carboxylato complexes, vanadium(V) carboxylato complexes require H2O2 to induce DNA cleavage while vanadium(IV) carboxylato complexes do not require H2O2 to induce DNA cleavage.As for vanadium phenanthroline derivative complexes, they can induce DNA cleavage in the presence and in the absence of H2O2. However, the DNA cleavage activity of the vanadium phenanthroline derivative complexes is greatly enhanced in the presence of H2O2. Reactive oxygen species (ROS) scavengers have also been used to ascertain the reactive species responsible for DNA cleavage. The hydroxyl radical and singlet oxygen species have been found to be the ROS that are responsible in the DNA cleavage reaction.